2012 American Control Conference (ACC) 2012
DOI: 10.1109/acc.2012.6315479
|View full text |Cite
|
Sign up to set email alerts
|

On a generalization of the proper orthogonal decomposition and optimal construction of reduced order models

Abstract: In this paper, the popular proper orthogonal decomposition (POD) without the usual integral or inner product constraints is extended to general Hilbert spaces, such as Sobolev spaces, using functional analytic methods. It is shown that a particular tensor product space is dense in the Hilbert space where the partial differential equation (PDE) solution lives. This allows approximating the PDE solution by tensors to any desired accuracy. Optimal approximation by these tensors is shown to result in the POD using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The POD is highly related to the theory of Hilbert-Schmidt operators. In [61,62], it is shown that the POD optimization problem is equivalent to finding the optimal approximation of a Hilbert-Schmidt operator related to u by a finite rank operator in the Hilbert-Schmidt norm. The POD basis functions can also be obtained from the eigenfunctions of the Hilbert-Schmidt integral operator [7] R u :…”
Section: The Proper Orthogonal Decomposition (Pod)mentioning
confidence: 99%
“…The POD is highly related to the theory of Hilbert-Schmidt operators. In [61,62], it is shown that the POD optimization problem is equivalent to finding the optimal approximation of a Hilbert-Schmidt operator related to u by a finite rank operator in the Hilbert-Schmidt norm. The POD basis functions can also be obtained from the eigenfunctions of the Hilbert-Schmidt integral operator [7] R u :…”
Section: The Proper Orthogonal Decomposition (Pod)mentioning
confidence: 99%
“…[39][40][41] In this case, the use of global bases may fail to capture the nonlinear local dynamics since it assumes the solution belongs to an affine subspace trying to minimize the Euclidean distance, and thus leads to poor approximate solution. 42,43 The performance of the global eigenfunctions becomes even worse when the local dynamic behavior changes significantly owing to nonlinear process parameters that change with space and time. Based on this observation, in order to capture the local dynamics of a complex nonlinear system more effectively, the eigenfunctions must be tailored to capture the local behavior of every portion of the solution trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…This could affect the accuracy and effectiveness of the developed low‐dimensional model, which might not be able to capture the local dynamics with a desired accuracy even with an unaffordable large number of eigenfunctions . In this case, the use of global bases may fail to capture the nonlinear local dynamics since it assumes the solution belongs to an affine subspace trying to minimize the Euclidean distance, and thus leads to poor approximate solution . The performance of the global eigenfunctions becomes even worse when the local dynamic behavior changes significantly owing to nonlinear process parameters that change with space and time.…”
Section: Introductionmentioning
confidence: 99%